Peranan Ilmu Komputer Dalam Perhitungan Uji Beton Di Laboratorium - Marwahyudi . (Universitas Sahid Surakarta, 2011)
ugar factory waste is pretty exciting stuff for in the analysis. Waste generated solid, gas, liquid still need to utilize the waste handling. On this occasion, the researcher triedto analyze molasses added to concrete materials. In this study, we created two groups of specimens will be compared to the results which one is better. Then the object testedsectioned with a compression test machine. After investigation it turned out the result showed the difference between concrete with molasses added material would be betterthan ordinary concrete. Top Calculation results divisive 15.63 Kg/cm2 test without added ingredients and 33.71 Kg/cm2 concrete with molasses added ingredients.